(untitled) (International Journal of Current Engineering and Technology, 2015)
The aim of this paper is to design a magnetorheological brake (MRB) system, which has potential to replace the existing automobile mechanical shoe-pedal brake system. The proposed brake system consists of rotary disks immersed in a MR fluid and enclosed in an electromagnet. The yield stress of the fluid varies as a function of magnetic field created by electric current passing through the electromagnet. The instantaneous increase in yield stress of fluid significantly increases the friction on the surfaces of rotating disks; thus generating a retarding braking torque. Unfortunately, MR fluids do not show linear increment in shear strength with increase in applied magnetic field, and finally shear strength gets saturated. Therefore in the present study, the non-linear behavior of shear strength and its saturation limits to estimate the braking torque exercised by MR brake have been incorporated. A parametric study considering various configurations of rotating disk and MR gap has been presented. Finally, based on analysis, merits of the multidisc MR brake have been highlighted.